Moral Value and Character Education Found In The Movie Upside-Down Magic - Hermika Manik; Natalia Widya Pasca Tarigan; Debora Putri Faomasi Liaptu Zega (English Language Teaching Prima Journal (ELT), 2023)
Moral values are very closely related to character education where the goal is to continuously shape and train individual abilities for self-improvement towards a better life.This journal discusses moral values and character education through the medium of a film entitled reverse magic at SMP Kemala Bhayangkari 1 Medan. This study aims to find moral values and character education in the film Upside-Down Magic and also to determine the relevance of moral values and character education contained in the film for class VIII students of SMP Kemala Bhayangkari 1 Medan. The type of research used is a type of qualitative research. The research instruments are note-taking and interviews. The source of the research data was the results of note taking obtained by students through watching films and interviews conducted by researchers with 21 grade VIII students and 2 teachers at SMP Kemala Bhayangkari 1 Medan. The results obtained by the researcher proved that there were moral values and character education that were found by the students themselves in the film entitled Upside-down magic and were proven to be relevant to students which were obtained through interviews with 21 students and 2 teachers. As for the implementation process, the researcher gave instructions to students to be able to discover moral values and character education for themselves in the Reverse magic film by showing the film directly to students.The results of this study have an impact on character education, namely increasing students' motivation to pay more attention to their character. Students are also inspired to apply moral values and character education in everyday life such as never giving up, discipline, courage and perseverance.